The roles of Nature for Woman’s Self-Awareness in Thomas Hardy’s Tess of The D’urbervilles: An Ecofeminism Approach - Alfarras, Riziq Prio; Br Kembaren, Arifah Pertiwi; MJ , Nurbasyirah; Purwarno, Purwarno (International Journal of English and Applied Linguistics (IJEAL), 2024)
Thomas Hardy's Tess of the d’Urbervilles illuminates profound connections between individuals, society, and the natural world. This study examines Hardy's narrative through an ecofeminism lens, investigating the role of nature in shaping women's self-awareness, particularly exemplified by the protagonist Tess. Utilizing qualitative descriptive methodology, the research delves into Tess's experiences, elucidating the intricate interplay between her consciousness, societal constraints, and environmental dynamics. The research reveals nature as a multifaceted backdrop for Tess's journey of self-discovery. Initially, her poignant encounter with the death of her horse, Prince, triggers a profound introspection, catalyzing her awareness of life's fragility and her own agency within the natural order. However, subsequent traumas, such as her violation in the forest, tarnish her perception of nature as a sanctuary, rendering it a poignant symbol of her suffering. Nevertheless, nature also offers Tess moments of solace and renewal. Her immersion in farm life provides a conduit for reconnecting with the rhythms of the earth, fostering resilience and empowerment amidst adversity. Moreover, nature becomes a refuge from societal judgment, albeit simultaneously serving as a poignant reminder of her past. Through Tess's odyssey, Hardy underscores the intimate bond between women and nature, shedding light on their vulnerability within patriarchal structures. This research contributes to the discourse on ecofeminism in literature by elucidating how nature shapes women's self-awareness and agency, advocating for a nuanced understanding of their complex relationship. Ultimately, it underscores the need for more equitable and empowering connections between women and the natural world.